Assessment of customer’s perception and expectations of service quality in Tanzania’s commercial banks: The case of Azania bank - Mwandosya, Joyce E. (Mzumbe University, 2024)
Dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the Degree of Master’s of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.